A new iterative detection algorithm for layered space-time receiver in frequency selective fading MIMO channels - Yu, Fei; He, Shiwen; Ba, Teer; Yang, Luxi (Proceedings (International Conference on Advanced Technologies for Communications), 2013)
The use of multiple antenna systems can increase system capacity in Rayleigh fading environments. The V-BLAST(Vertical Bell Laboratories Layered Space-Time) system which can attain great performance while maintaining low implementation complexity has been paying more attention in recent years. However, the performance of a practical FS-BLAST system with a successive interference cancellation detector suffers great degradation due to the error propagation. In this paper, we propose a novel FS-BLAST detection algorithm which use ML(Maximum Likelihood) searching in iterative detection scheme. From the simulation, we can see that it outperforms the traditional FS-BLAST algorithm.